Credit portfolio management - Smithson, Charles (John Wiley, 2003)
Credit risk. A number of market factors are causing revolutionary changes in the way it is measured and managed at financial institutions. Charles Smithson, author of the bestselling Managing Financial Risk, introduces a portfolio management approach to credit in his latest book. Understanding how to manage the inherent risks of this market has become increasingly important over the years. Credit Portfolio Management provides readers with a complete understanding of the alternative approaches to credit risk measurement and portfolio management. This definitive guide discusses the pricing and managing of credit risks associated with a variety of off-balance-sheet products such as credit default swaps, total return swaps, first-to-default baskets, and credit spread options; as well as on-balance-sheet customized structured products such as credit-linked notes, repackage notes, and synthetic collateralized debt obligations (CDOs). Filled with expert insight and advice, this book is a must-read for all credit professionals.